2015
DOI: 10.2478/aoa-2014-0033
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modal Acoustic Flow Decomposition Examined in a Hard Walled Cylindrical Duct

Abstract: Flow fields could be of great interest in the study of sound propagation in aeroengines. For ducts with rigid boundaries, the fluid-resonant category may contribute significantly to unwanted noise. An understanding of the multi-modal propagation of acoustic waves in ducts is of practical interest for use in the control of noise in, for example, aero-engines, automotive exhaust and heating or ventilation systems. The purpose of our experiments was to test the acoustic energy transmission of duct modes based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The details of using the phase-locked particle image velocimetry along with applying the Proper Orthogonal Decomposition method [13] are shown in the papers by Mickiewicz [11,12] and could be used for such a comparison.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…The details of using the phase-locked particle image velocimetry along with applying the Proper Orthogonal Decomposition method [13] are shown in the papers by Mickiewicz [11,12] and could be used for such a comparison.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…Vortex flow can be introduced in fluid systems by modification of the path of flow in order to achieve desired effects. Such modifications include introduction of holes with sharp edges [2], barriers in the path of flow [3], or sudden contraction or expansion as is the case with the SEC [4]. Applications of this phenomenon in vortex motion have been successfully studied by Smith et al, [5] who identified two scattering mechanisms that allow neighbouring modes to interact; scattering occurs at significantly lower frequencies when the mean flow is present; an exchange of energy between mean flow and acoustic field occurs during scattering.…”
Section: Introductionmentioning
confidence: 99%
“…In conventional acoustic metrology, the analysis of acoustic fields concerns the distribution of pressure levels (scalar variable), however in a real acoustic field, both the scalar (acoustic pressure) and vector (acoustic particle velocity) effects are closely related (Weyna, 2014). Only when the acoustic field is described by both the potential and kinetic energies, it is possible to understand the mechanisms of propagation, diffraction and scattering of acoustic waves on obstacles, as a form of energy image (Weyna, 2003).…”
Section: Introductionmentioning
confidence: 99%